4-Ferrocenylaniline-based ROS-responsive prodrugs with anticancer activity - Xu, Honggui; Annamadov, Saparmyrat; Mokhir, Andriy (Journal of Organometallic Chemistry, 2022)
Ferrocene derivatives often exhibit anticancer activity. For example, our group has developed aminoferrocene-based (AF) prodrugs, which are activated in the presence of reactive oxygen species (ROS), present in large quantities in cancer cells. The activation reaction leads to formation of AF's, whose redox potential is shifted by 300–400 mV to negative values as compared to the parent AF prodrugs. Correspondingly, these drugs are very electron rich and can, therefore, act as catalysts of generation of highly toxic hydroxyl radicals (HO●) from H2O2. That contributes to the cytotoxicity of AF prodrugs. Unfortunately, AF's are chemically very unstable. Therefore, their lifetime in cells is < 1 h that limits the anticancer activity of the AF prodrugs. In this paper we report on new 4-ferrocenylaniline-based (4-FcAn) prodrugs. These are activated in the presence of ROS thereby releasing 4-FcAn. We confirmed that 4-FcAn is more electron rich than the corresponding prodrug (ΔE1/2 = 86 mV) and can generate HO● from H2O2 analogously to AF. Furthermore, we observed that (a) 4-ferrocenylanilines are substantially more stable (>6 h) than AF's and (b) the corresponding prodrugs are substantially more active than the structurally related AF prodrugs. We found that, analogously to AF prodrugs, the new prodrugs exhibit their anticancer activity via generation of ROS in cancer cells.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Anticancer; Ferrocene; Prodrug; Reactive oxygen species; Redox catalysis